Kajian Hukum Pidana Dalam Penipuan Jual Beli Akun Permainan Online Melalui Media Sosial - Herrenauw, Jefferson Meiggers; Titahelu, Juanrico Alfaromona Sumarezs; Saimima, Judy Marria (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Fraud in the sale and purchase of online game game accounts, it is a legal obligation to straighten it out for the sake of creating an orderly civilized society and to try to prevent anti-social behavior, namely behavior that is contrary to the principles of social order and law. So that the problem of misuse of this technology does not become social unrest and is detrimental to the community.Purposes of the Research: The purpose of this study is to examine and explain fraud in the sale and purchase of online game accounts that can be qualified as perpetrators of criminal acts, to examine and explain the perpetrators of fraud in the sale and purchase of online game accounts being held criminally responsible. Methods of the Research: The method used is a normative juridical research method with a qualitative analysis type with an interactive analysis and conceptually tends to be directed at finding, identifying, managing, and analyzing legal materials to understand the meaning, significance, and relevance.Results of the Research: The results show that fraud in buying and selling online game accounts can be categorized as a criminal act of fraud because of the fact that fraud in buying and selling online game accounts has fulfilled the elements of fraud in Article 378 of the Criminal Code as well as in Article 28 paragraph (1) of the ITE Law. Fraud perpetrators can be held criminally responsible based on the condition that digitally impose criminal liability for fraud, namely the fulfillment of all elements of crime according to criminal law and/or according to the ITE Law. The police as law enforcement officers must really understand the ITE Law so that they can qualify online game account trading fraud as a criminal act of fraud so that the perpetrators can be processed to account for their actions. Gamers who are victims of online game account trading scams report this to the authorities so that they can be processed according to applicable law.